Strategi Humas PT Tempat Berkarya Indonesia dalam Membangun Brand Image Edukatif Melalui Konten Media Sosial Instagram - Aulia, Raden Roro Fatimah Azzahra; Santoso, Hudi; Saleh, Amiruddin; Harpin, Rici Tri; Manisya, Nabila; Maharani, Khalila Zahra (Bahasa Indonesia, 2025)
This study analyzes the public relations strategy implemented by PT Tempat Berkarya Indonesia in building an educational brand image through Instagram social media content. The research focuses on the public relations strategy for creating educational content and identifying factors that influence content development. A qualitative case study approach is used, with data collected through in-depth interviews with the public relations team and social media managers, as well as direct observation of Instagram content, including reels, feeds, and stories. The findings reveal that PT Tempat Berkarya Indonesia effectively utilizes an educational content strategy through informative and visually engaging posts that resonate with the audience's needs. Additionally, factors such as social media trends, audience preferences, and the company’s educational objectives significantly influence the planning and execution of content. This study demonstrates that Instagram serves as a vital tool for the company in building a cohesive and impactful educational brand image that consistently attracts audience attention.